(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The history of floristic research related to dry meadows in the Middle Russian province of the Forest-Steppe in Ukraine since the XIX century was analysed. More than 200 literary sources were included to this investigation. There are general works by naturalists, floristic lists and distribution data of rare species on the territory of Sumy and Kharkiv geobotanical districts. We concluded that the most works until 1900 were floristic. Howewer, the total number of works provided data about rare species began to increase. From the 30’s of the last century, scientists worked in detail with plant geography and taxonomy. The next direction is the study of plant communities, which has been actively developing since the 60’s. The nature protection direction began to develop after the establishment the State Committee for Nature Protection in 1967. Since 2000, there has been a sharp jump in the number of works that are somehow related to the flora of dry meadows. Today we can find more conservation works, especially devoted to the study of botanical reserves. It was established that the largest number of works connected with the territories of Kharkiv, Sumy, Bohodukhiv, Okhtyrka, Trostyanets. Since the end of the last century, important centers of long-term research of dry meadows are biological station of the Faculty of Biology of V. N Karazin Kharkiv National University in the village Gaidary (Kharkiv region) as well as biological station "Vakalivshchyna" of Sumy State Pedagogical University named after A. S Makarenko (Sumy region). A common feature of most of the studied works is that the authors write about the need to preserve dry meadows, because due to excessive agricultural activity they are almost completely plowed. An analysis of published data, we see that dry meadows were studied in fragments.